Vertebral artery stump syndrome: A 7-year follow-up case report - Michiru Katayama, MD; Hideki Endo, MD, PhD; Megumi Matsuda, MD; Kenji Kamiyama, MD; Toshiaki Osato, MD; Hirohiko Nakamura, MD, PhD (Radiology Case Reports, 2022)
Vertebral artery stump syndrome is rare, but one of the most important causes of posterior circulation stroke. To our knowledge, no optimal treatment for vertebral artery stump syndrome has been established, and there are no reports of long-term follow-up. We describe a 69-year-old man with vertebral artery stump syndrome who attended our hospital because of vertigo. Magnetic resonance imaging detected right cerebellar infarcts. Digital subtraction angiography revealed severe stenosis (functional obstruction) at the origin of the right vertebral artery, with distal antegrade collateral flow from the deep cervical artery. We started him on argatroban and cilostazol, but symptoms recurred after 1 month. We changed from cilostazol to aspirin and clopidgrel, then terminated aspirin 1 month after recurrence. He continued on clopidgrel, and follow-up after 7 years showed no recurrence, including asymptomatic lesions.